Restructuring of Commercial Bank Debt by Developing Countries : Lessons from Recent Experience - El-Erian, Mohamed (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1993)
A number of developing countries, including some of the largest debtors, have recently completed comprehensive debt and debt service restructuring packages with their commercial bank creditors. The experience of these countries provides important lessons for other countries that are just embarking on discussions to normalize their external payments situation. Following a brief description of the framework of the international debt strategy, this paper discusses the main lessons, distinguishing between those that are relevant to the process of negotiation and those relevant to the structure of the package being negotiated. This is a Paper on Policy Analysis and Assessment and the authors) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the authors) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.